Dynamics of racism in Peru: the cultural perspective of Gonzalo Portocarrero - Vich, Víctor (2020)
Gonzalo Portocarrero constructed three metaphors to explain the dynamics of racism in Peru, that is, to try to describe its mode of operation and the particular way in which it had been produced (and established) in social practices and in the social imaginary. The three metaphors were the following: the invisible foundation, the ghost of the patron and the utopia of whitening or «blanqueamiento». This essay explains each of them and brings them into dialogue with some of the main contributions that, in order to understand it, have been proposed in Peru and in current critical theory.